The Getting of Wisdom - Richardson, Henry Handel, 1870-1946 (Salt Lake City, UT : Project Gutenberg, 2003)
"The Getting of Wisdom" by Henry Handel Richardson is a novel first published in 1910. Twelve-year-old Laura Rambotham leaves her country home for an elite Melbourne boarding school, where her imaginative nature and humble circumstances clash with the wealthy students' harsh social codes. Through humiliation and isolation, Laura navigates the rigid world of 1890s girls' education, questioning authority, morality, and her own values. Based on Richardson's own boarding school experiences, this Australian classic explores one girl's struggle for authenticity and freedom in an unforgiving environment. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Getting_of_Wisdom
Release date is 2003-02-01
Produced by Col Choat. HTML version by Al Haines.
Keywords: Autobiographical fiction; Australia -- Fiction; Young women -- Fiction; Bildungsromans; Melbourne (Vic.) -- Fiction